Framing the Human Dimension in Cybersecurity - J. Nixon; B. McGuinness (EAI Endorsed Transactions on Security and Safety, 2013)
The advent of technologies that can seamlessly operate in different environments with differing levels of security present new challenges to the cybersecurity specialist seeking to ensure the safety of data, process or output of a complex system. This paper reviews the human dimension of cybersecurity. The Human Factors Integration (HFI) framework is employed as a structure with which to consider the many ways in which the human can differentially affect the security of a system both positively and negatively. We conclude that when the human factors element is analysed when specifying and designing secure and safe systems, it is far more likely that the human can assist and increase the overall level of security. As in other high technology sectors such as aviation or petrochemical, if not considered, the human can often ‘bulldoze’ through the most carefully considered and designed security or safety barriers